O11.2 Overcoming the ambiguity of sexual partnership type: a novel categorisation using data from britain's 3rd national survey of sexual attitudes and lifestyles (natsal-3). (13th September 2015) - Mercer, CH; Jones, KG; Johnson, AM; Lewis, R; Mitchell, KR; Clifton, S; Tanton, C; Sonnenberg, P; Wellings, K; Cassell, JA; Estcourt, CS
Abstract : Background: The labels 'casual' and 'regular' partners are routinely used in both research and clinical contexts, yet considerable subjectivity surrounds the definition of different types of partnership in both professional and lay contexts, rendering comparison of audit and research findings problematic. We use national probability survey data to distinguish between different types of partnership, and examine the association between the resulting typology and reported STI diagnosis/es. Methods: 15, 162 people aged 16–74y resident in Britain participated in Natsal-3 undertaken 2010–2012. Computer-assisted-self-interview was used for sensitive questions including those relating to participants' (max.) three most recent partners (N = 12, 167 partners/past year). ANOVA and regression were used to test for differences in partnership duration and perceived likelihood of sex again across 20 'Partnership Progression Types' (PPTs) derived from reported relationship status at first/most recent sex with partners. Multivariable regression examined whether reporting STI diagnosis/es varied by partnership type after adjusting for partner numbers (all past year). Results: Four summary partnership types were identified from the 20 PPTs with median[IQR] durations and likelihoods of sex again (%), respectively, of:(1)'Long-term' = 175 months [83–323], 96.9% likelihood of sex again; (2)'Ex-steady' = 38 months [16–90], 44.9%; (3)'Now steady' = 17 months [6–41], 74.4%; (4)'Currently casual' = 3 months [0–14], 43.9%. These thresholds neither varied significantly by gender nor sexual identity, but did by age and sexual health clinic attendance. Reporting STI diagnoses varied according to the combination of partnership types experienced, including after adjusting for partner numbers, e.g. AOR for reporting STI diagnoses among men with both 'currently casual' and 'ex-steady' partners: 6.07 (95% CI: 1.41–26.1) vs. men with only 'currently casual' partners. Conclusion: Two survey questions enabled identification of four distinct types of sexual partnership in the British population. This typology is a valuable first step in defining partnership type, benefitting both research and practice, especially given recent moves towards more detailed reporting of sexual risk and partner notification outcomes. Disclosure of interest statement: AMJ has been a Governor of the Wellcome Trust since 2011. The other authors declare that they have no conflicts of interest.